The Global Climate Change Knowledge and Practices of 4-H and Extension Youth Educators - Roberta H Hunter; Hui-Hui Wang; Bryanna J Nelson; Devarati Bhattacharya (Journal of International Agricultural and Extension Education, 2022)
4-H and Extension educators who work with youth are uniquely positioned to help them meaningfully learn about global climate change (GCC) in a way that connects to their everyday lives and interests. Yet we don’t have a baseline understanding of these educators’ knowledge of GCC or how they teach about it. This paper presents brief findings of a study intended to fill that gap in knowledge. Educators from six states responded to an online survey in 2020. GCC knowledge varied by topic and by educator instructional focus, with STEM and Civic Engagement educators scoring highest. Questions about greenhouse gasses and long-term air temperature changes had the lowest number of correct answers. Responses to open ended questions in the survey indicated a moderate number of educators believed that GCC is anthropogenic. Most educators avoided teaching about GCC or touched on it briefly. Those that did teach about GCC indicated their main motivation is that such instruction benefits youth, followed by care for the earth. Recommendations for professional development, such as making opportunities contextualized to the instructional focus and the geographic location are shared.
Keywords: climate change; informal educators; youth; 4-H; Extension